Flame retardant resin composition, as well as molded product, wire and cable, each including the same

JP2024109486A5Active Publication Date: 2025-02-21NISSHIN CHEM IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023014308
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-02-01
Publication Date
2025-02-21
Estimated Expiration
2043-02-01

AI Technical Summary

Technical Problem

Conventional polyolefin-based flame-retardant resin compositions face challenges in achieving high flame retardancy while maintaining moldability and mechanical properties, particularly when increased filler content is required to meet international standards, leading to issues with fluidity and tensile strength during extrusion molding.

Method used

A polyethylene-based flame-retardant resin composition incorporating an inorganic flame retardant and a silicone-acrylic graft copolymer resin, which improves flame retardancy and slipperiness with a small amount of additives, enhancing both properties without compromising moldability.

Benefits of technology

The composition achieves improved flame retardancy and tactile feel compared to compositions with only inorganic flame retardants, ensuring excellent moldability and mechanical properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a polyethylene-based flame retardant resin composition that includes an inorganic flame retardant and a silicon acrylic graft copolymer resin which, when added in small quantities, offers improved flame resistance and sliding characteristics, as well as a molded product, a wire and a cable, each including the same.SOLUTION: A flame retardant resin composition contains the following components (I), (II), and (III). (I) a polyethylene resin: 100 pts.mass, (II) an inorganic flame retardant: 50-300 pts.mass, and (III) a silicone acryl graft copolymer resin: 1-20 pts.mass, which is a copolymer of a polyorganosiloxane represented by the formula (1), and at least one monomer selected from acrylate monomers and methacrylate monomers.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flame-retardant resin composition, more particularly to a polyethylene-based flame-retardant resin composition containing an inorganic flame retardant and a silicone-acrylic graft copolymer resin, and to a molded article, and an electric wire and cable using the same. [Background technology]

[0002] Polyvinyl chloride resin compositions have been used as flame-retardant materials for electric wire coverings and the like. However, polyvinyl chloride resin compositions have the drawback of generating toxic halogen-containing gases when burned in the event of a fire or during waste incineration. Therefore, development is underway to make olefin-based resins flame-retardant and use them for electric wire applications and the like.

[0003] Resin compositions (non-halogen flame-retardant materials) in which metal hydrates such as aluminum hydroxide or magnesium hydroxide are blended with polyolefin resins have been proposed. For example, International Publication No. 2013 / 107971 discloses a non-halogen flame-retardant polyethylene resin, which contains maleic anhydride grafted polyethylene and uses a coupling agent containing an ethylene-acrylic ester-maleic anhydride terpolymer for the purpose of maintaining mechanical properties even in high-temperature and high-humidity environments. In addition, JP 2015-118817 A and International Publication No. 2018 / 74233 A use a non-halogen resin and an aliphatic amide or stearic acid as a lubricant.

[0004] On the other hand, due to differences in building structure and the like, a higher flame retardancy grade is required for flame retardant materials for electric wires or cables in Europe, the United States, and the like than in Japan. In order to improve the flame retardancy of halogen-free flame retardant polyethylene resins, it is generally necessary to increase the content of fillers such as metal hydrates. JP 2012-102307 A discloses a flame retardant resin composition in which particles of metal hydroxides such as magnesium hydroxide are surface-treated with a fatty acid-based material and added to a polyolefin-based resin, in order to obtain excellent water resistance even when the metal hydroxides are highly loaded.

[0005] However, in a halogen-free flame-retardant polyethylene resin, if the content of an inorganic flame retardant is increased to improve flame retardancy, the fluidity during extrusion molding becomes insufficient, making it difficult to ensure molding processability, and also making it difficult to ensure mechanical properties such as tensile strength at break. Conventional flame-retardant resin compositions using magnesium hydroxide as a flame retardant are not necessarily sufficient as materials that are excellent in carbon dioxide whitening resistance and also ensure fluidity during molding processing and mechanical properties such as tensile strength at break.

[0006] JP 2021-147555 A discloses a polyolefin-based flame-retardant resin composition that contains a combination of a fatty acid-treated metal hydrate and a phosphate-treated metal hydrate, including at least one of fatty acid-treated magnesium hydroxide and phosphate-treated magnesium hydroxide. However, there is a demand for the development of a flame-retardant resin composition that can more easily improve flame retardancy. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2013 / 107971 [Patent Document 2] JP 2015-118817 A [Patent Document 3] International Publication No. 2018 / 74233 [Patent Document 4] JP 2012-102307 A [Patent Document 5] Patent Publication No. 2021-147555 Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a polyethylene-based flame-retardant resin composition containing an inorganic flame retardant and a silicone acrylic graft copolymer resin that can improve not only flame retardancy but also slipperiness by adding a small amount of the same, and a molded article, and an electric wire and cable using the same. [Means for solving the problem]

[0009] As a result of intensive research into achieving the above object, the present inventors have found that a polyethylene-based flame-retardant resin composition containing an inorganic flame retardant and a silicone acrylic graft copolymer resin can solve the above problems, thereby completing the present invention.

[0010] Accordingly, the present invention provides the following flame-retardant resin composition, and a molded article, electric wire, and cable using the same. A flame-retardant resin composition comprising the following components (I), (II), and (III): (I) polyethylene resin: 100 parts by mass, (II) inorganic flame retardant: 50 to 300 parts by mass, and (III) 1 to 20 parts by mass of a silicone acrylic graft copolymer resin which is a copolymer of a polyorganosiloxane represented by the following formula (1) and at least one monomer selected from an acrylic acid ester monomer and a methacrylic acid ester monomer, and in which the mass ratio of the polyorganosiloxane to the acrylic acid ester unit and the methacrylic acid ester unit is 50:50 to 90:10: A flame-retardant resin composition comprising [ka] (In the formula, R 1are each independently a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, R 2 is a mercapto group, an alkyl group having 1 to 6 carbon atoms having an acryloxy group or a methacryloxy group, or a vinyl group; X's are each independently a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a hydroxyl group; a is a positive number from 1 to 10,000, b is a positive number from 0.1 to 1000, and c is 2; however, the bonding order of the siloxane units in the above formula (1) is not limited to the above. Effect of the Invention

[0011] The flame-retardant resin composition of the present invention, which is obtained by blending a silicone acrylic graft copolymer resin with a polyethylene resin, has improved flame retardancy and improved tactile feel compared to a composition which contains only an inorganic flame retardant. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention relates to a flame-retardant resin composition comprising (I) a polyethylene resin, (II) an inorganic flame retardant, and (III) the above-mentioned silicone acrylic graft copolymer resin. Each component is described in detail below.

[0013] (I) The polyethylene resin may be composed of one or more selected from ethylene homopolymers and copolymers mainly composed of ethylene. Examples of ethylene homopolymers include low density polyethylene, linear low density polyethylene, linear low density polyethylene, and high density polyethylene. From the viewpoint of light weight and excellent moldability, polyethylene having a density of 0.910 to 0.965 g / cm3 is preferred. 3and the melt mass flow rate at 190°C and a load of 2.16 kg is preferably 0.01 to 200 g / 10 min. If the melt mass flow rate at 190°C and a load of 2.16 kg is within the above range, there is no risk of problems occurring in the fluidity of the resin composition and the surface appearance of the molded product. More preferably, the melt mass flow rate at 190°C and a load of 2.16 kg is 0.01 to 60 g / 10 min. The melt mass flow rate is measured using an extrusion type plastometer or the like in accordance with the method specified in JIS K7210-1:2014. The durometer hardness (D) of the polyethylene resin is preferably 15 to 90, more preferably 20 to 85, and even more preferably 20 to 70.

[0014] As the polyethylene resin, commercially available products can be used, and examples thereof include Novatec L LUE320, Novatec LDZE4K, and Novatec LDZF33 manufactured by Nippon Polyethylene; UBE, polyethylene L719, L518, L618, and C410 manufactured by Ube Maruzen Polyethylene; and Sumikathene C215, G201, G109, F236-0, and F411-0 manufactured by Sumitomo Chemical.

[0015] Examples of copolymers containing ethylene as a main component include random copolymers of ethylene and one or more α-olefins other than ethylene, block copolymers of ethylene and one or more α-olefins other than ethylene, ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid ester copolymers, and ethylene-(meth)acrylic acid copolymers. Among copolymers containing ethylene as a main component, from the viewpoint of light weight and excellent moldability, ethylene copolymers having a melt mass flow rate of 0.01 to 200 g / 10 min at 190° C. and a load of 2.16 kg are preferred. If the melt mass flow rate at 190° C. and a load of 2.16 kg is within the above range, there is no risk of problems occurring in the fluidity of the resin composition and the surface appearance of the molded product, and it is more preferred that it is 0.01 to 60 g / 10 min. Examples of α-olefins other than ethylene include propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.

[0016] In the case of ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid copolymer, and ethylene-(meth)acrylic acid ester copolymer, the melt mass flow rate measured at a temperature of 190° C. and a load of 2.16 kg in accordance with JIS K7210 (1999) is preferably 50 g / 10 min or less, more preferably 0.05 to 30 g / 10 min, and even more preferably 0.1 to 10 g / 10 min. If the melt mass flow rate is too high, the mechanical properties are reduced, and if it is too low, the moldability is deteriorated.

[0017] The (meth)acrylic acid ester in the ethylene-(meth)acrylic acid ester copolymer may be an ester of (meth)acrylic acid and an alcohol having 1 to 8 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.

[0018] The ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid copolymer, and ethylene-(meth)acrylic acid ester copolymer contain COOR type functional groups. The copolymers have the following characteristics: (1) During pyrolysis, a decarbonation reaction occurs, and the material becomes CO2. In other words, it produces non-combustible gas without releasing combustion energy. (2) Because it is hydrophilic, the interfacial strength with the inorganic flame retardant metal hydrate is high, and even if a large amount of inorganic flame retardant is added, the degree of deterioration in physical properties is small. (3) The comonomer copolymerized with ethylene is bulky, so that it has high tolerance to inorganic flame retardants, and even if a large amount of inorganic flame retardant is added, the degree of deterioration in physical properties is small. The copolymer is advantageous as a base material for a non-halogen flame-retardant resin composition because of the above-mentioned characteristics. In addition, the present invention is characterized in that the crosslinked resin composition is produced by melt kneading at a low temperature, and the use of these resins can suppress the drawback of reduced manufacturability due to the expression of adhesive ability during the production of the composition.

[0019] (II) Examples of inorganic flame retardants include inorganic powders for flame retardants, such as metal hydroxides, metal oxides, metal carbonate compounds, metal powders, boron compounds, and low-melting glass. 50 The value is used as the average particle size (μm), and it is more preferable that it is 0.5 to 5 μm. The particle size was measured by a laser diffraction type.

[0020] Examples of the metal hydroxide include aluminum hydroxide, magnesium hydroxide, dolomite, hydrotalcite, calcium hydroxide, barium hydroxide, and zirconium hydroxide. Aluminum hydroxide and magnesium hydroxide are preferable. The metal hydroxide may be surface-treated with a higher fatty acid such as stearic acid or a silane coupling agent. By using such a surface-treated metal hydroxide, the dispersibility when kneading with the base polymer can be improved. The metal hydroxide may be a commercially available product. Magnesium hydroxide surface-treated with a silane coupling agent is preferable, and examples of commercially available products include Kisuma 5L, Kisuma 5N, and Kisuma 5P (all trade names, manufactured by Kyowa Chemical Industry Co., Ltd.), and Magseeds S series (trade name, manufactured by Konoshima Chemical Industry Co., Ltd.). Examples of untreated magnesium hydroxide include Kisuma 5 (trade name, manufactured by Kyowa Chemical Industry Co., Ltd.), and Magnifin H5 (trade name, manufactured by Albemarle Corporation).

[0021] Examples of metal oxides include zinc molybdate, molybdenum trioxide, zinc stannate, tin oxide, aluminum oxide, iron oxide, titanium oxide, manganese oxide, zirconium oxide, zinc oxide, molybdenum oxide, cobalt oxide, bismuth oxide, chromium oxide, nickel oxide, copper oxide, and tungsten oxide.

[0022] Examples of the metal carbonate compound include zinc carbonate, magnesium carbonate, calcium carbonate, barium carbonate, basic magnesium carbonate, aluminum carbonate, iron carbonate, cobalt carbonate, and titanium carbonate.

[0023] Examples of metal powders include aluminum, iron, titanium, manganese, zinc, molybdenum, cobalt, bismuth, chromium, nickel, copper, tungsten, and tin.

[0024] Examples of boron compounds include zinc borate, zinc metaborate, barium metaborate, boric acid, and borax.

[0025] Examples of the low-melting glass include glassy compounds such as Seapley (Boxey Brown), hydrated glass SiO2-MgO-H2O, PbO-B2O3, ZnO-P2O5-MgO, P2O5-B2O3-PbO-MgO, P-Sn-OF, PbO-V2O5-TeO2, Al2O3-H2O, and lead borosilicate.

[0026] The amount of the inorganic flame retardant (II) is 50 to 300 parts by mass, preferably 80 to 250 parts by mass, and more preferably 100 to 200 parts by mass, per 100 parts by mass of the polyethylene resin (I). If the amount of the inorganic flame retardant is less than the lower limit, good results cannot be obtained in the oxygen index or flame retardancy test, whereas if the amount of the inorganic flame retardant is more than the upper limit, moldability is deteriorated.

[0027] The silicone acrylic graft copolymer resin (III) of the present invention is preferably a copolymer of a polyorganosiloxane represented by the following formula (1) and an acrylic acid ester monomer or a methacrylic acid ester monomer. It is preferably obtained by emulsion graft polymerization and drying of a mixture of (i) a polyorganosiloxane represented by the following formula (1) and (ii) a (meth)acrylic acid ester monomer, or a mixture of the above components (i) and (ii) and an optional functional group-containing monomer (iii) copolymerizable with component (ii).

[0028] (i) The polyorganosiloxane is represented by the following formula (1). [ka] In the formula, R 1 are each independently a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, R 2is a mercapto group, an alkyl group having 1 to 6 carbon atoms having an acryloxy group or a methacryloxy group, or a vinyl group, X is each independently a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a hydroxyl group, a is a positive number from 1 to 10,000, b is a positive number from 0.1 to 1000, and c is 2. In the above formula (1), the bonding order of the siloxane units is not limited to the above, and the individual siloxane units may form block units or be bonded randomly.

[0029] In the above formula, R 1 are each independently a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, and are preferably a linear, branched or cyclic alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms. Examples of the alkyl groups include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, tetradecyl, hexadecyl, and octadecyl groups; cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl groups; alkenyl groups such as vinyl and allyl groups; aryl groups such as phenyl, tolyl, and naphthyl groups; alkenylaryl groups such as vinylphenyl groups; aralkyl groups such as benzyl, phenylethyl, and phenylpropyl groups; and alkenylaralkyl groups such as vinylbenzyl and vinylphenylpropyl groups, or groups in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine, bromine, and chlorine, acryloxy groups, methacryloxy groups, carboxyl groups, alkoxy groups, alkenyloxy groups, amino groups, and alkyl, alkoxy, or (meth)acryloxy-substituted amino groups. 1 is preferably a methyl group.

[0030] R 2 is a mercapto group, an alkyl group having 1 to 6 carbon atoms substituted with an acryloxy group or a methacryloxy group, or a vinyl group. For example, a mercaptopropyl group, an acryloxypropyl group, a methacryloxypropyl group, a vinyl group, etc. are preferred.

[0031] X's are each independently a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a hydroxyl group. The unsubstituted or substituted monovalent hydrocarbon group having 1 to 20 carbon atoms is preferably R 1 Examples of the alkoxy group having 1 to 20 carbon atoms include a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a hexyloxy group, a heptyloxy group, an octyloxy group, a decyloxy group, and a tetradecyloxy group. X is preferably a hydroxyl group, a methyl group, a butyl group, a phenyl group, or a methoxy group.

[0032] In the above formula (1), if a is a number greater than 10,000, the strength of the resulting cured product will be insufficient. a is an integer from 1 to 10,000, and preferably an integer from 500 to 6000. If b is a number less than 0.1, the flexibility of the cured product will be poor, and if it is a number greater than 1,000, the tear strength of the cured product will decrease. b is a positive number from 0.1 to 1,000, preferably a positive number from 0.1 to 100, more preferably a positive number from 0.5 to 10, and even more preferably a positive number from 1 to 5. c is 2.

[0033] Preferably, at least two, more preferably two to four, of the X's at both ends in the above formula (1) are hydroxyl groups or alkoxy groups. The alkoxy groups are preferably alkoxy groups having 1 to 4 carbon atoms, more preferably methoxy groups. More preferably, the compound has silicon atom-bonded hydroxyl groups at both ends.

[0034] The polyorganosiloxane (i) is preferably used in the form of an emulsion, and may be a commercially available product or may be synthesized. When synthesizing, a known emulsion polymerization method may be performed. For example, a cyclic organosiloxane or an α,ω-dihydroxysiloxane oligomer, an α,ω-dialkoxysiloxane oligomer, an alkoxysilane, etc., which may have a fluorine atom, a (meth)acryloxy group, a carboxyl group, a hydroxyl group, or an amino group, and a silane coupling agent represented by the following general formula (2) are emulsified and dispersed in water using a surfactant, and then a catalyst such as an acid is added as necessary to carry out a polymerization reaction, whereby the polyorganosiloxane can be easily synthesized. R 3 (4-e-f) R 4 f Si(OR 5 ) e (2) In the above formula (2), R 3 is a monovalent organic group having a polymerizable double bond, such as a mercapto group, an alkyl group having 1 to 6 carbon atoms substituted with an acryloxy group or a methacryloxy group, or a vinyl group; R 4 is an alkyl group having 1 to 4 carbon atoms, and R 5 is an alkyl group having 1 to 4 carbon atoms, e is 2 or 3, f is 0 or 1, and e+f is 2 or 3.

[0035] Examples of the cyclic organosiloxane include hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), dodecamethylcyclohexasiloxane (D6), 1,1-diethylhexamethylcyclotetrasiloxane, phenylheptamethylcyclotetrasiloxane, 1,1-diphenylhexamethylcyclotetrasiloxane, 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, 1,3,5,7-tetracyclohexyltetramethylcyclotetrasiloxane, tris(3,3,3-trifluoropropyl)trimethylcyclotrisiloxane, 1,3,5,7-tetra(3-methacryloxypropyl)tetramethylsiloxane, and the like. Examples of the tetrasiloxane include chlorotetrasiloxane, 1,3,5,7-tetra(3-acryloxypropyl)tetramethylcyclotetrasiloxane, 1,3,5,7-tetra(3-carboxypropyl)tetramethylcyclotetrasiloxane, 1,3,5,7-tetra(3-vinyloxypropyl)tetramethylcyclotetrasiloxane, 1,3,5,7-tetra(p-vinylphenyl)tetramethylcyclotetrasiloxane, 1,3,5,7-tetra[3-(p-vinylphenyl)propyl]tetramethylcyclotetrasiloxane, 1,3,5,7-tetra(N-acryloyl-N-methyl-3-aminopropyl)tetramethylcyclotetrasiloxane, and 1,3,5,7-tetra(N,N-bis(lauroyl)-3-aminopropyl)tetramethylcyclotetrasiloxane. Octamethylcyclotetrasiloxane and decamethylcyclopentasiloxane are preferably used.

[0036] Examples of silane coupling agents include vinyl silanes such as vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tripropoxy silane, vinyl triisopropoxy silane, vinyl methyl dimethoxy silane, and vinyl methyl diethoxy silane; γ-(meth)acryloxypropyl trimethoxy silane, γ-(meth)acryloxypropyl triethoxy silane, γ-(meth)acryloxypropyl tripropoxy silane, γ-(meth)acryloxypropyl triisopropoxy silane, and γ-(meth)acryloxypropyl triisopropoxy silane. Examples of the silanes include acrylic silanes such as dimethylpropyl tributoxy silane, γ-(meth)acryloxypropyl methyl dimethoxy silane, γ-(meth)acryloxypropyl methyl diethoxy silane, γ-(meth)acryloxypropyl methyl dipropoxy silane, γ-(meth)acryloxypropyl methyl diisopropoxy silane, and γ-(meth)acryloxypropyl methyl dibutoxy silane; and mercapto silanes such as γ-mercaptopropyl methyl dimethoxy silane and γ-mercaptopropyl trimethoxy silane. Alternatively, oligomers obtained by condensation polymerization of these may be more preferable because they suppress the generation of alcohol. Here, (meth)acryloxy refers to acryloxy or methacryloxy. The amount of the silane coupling agent is preferably 0.01 to 20 parts by mass, and more preferably 0.01 to 5 parts by mass, per 100 parts by mass of the cyclic organosiloxane, α,ω-dihydroxysiloxane oligomer, α,ω-dialkoxysiloxane oligomer, or alkoxysilane.

[0037] By copolymerizing the above-mentioned cyclic organosiloxane or the like with the silane coupling agent represented by the above general formula (2), (R 2 (R 1 )SiO 2 / 2 This gives a polyorganosiloxane having the above formula (1) containing the aryloxy group unit, and the effect of grafting the monomer of component (ii) or (iii) is obtained.

[0038] In the above reaction, a known polymerization catalyst may be used as the catalyst for polymerization. Among them, strong acids are preferred, and examples thereof include hydrochloric acid, sulfuric acid, dodecylbenzenesulfonic acid, citric acid, lactic acid, and ascorbic acid. Dodecylbenzenesulfonic acid having emulsifying ability is preferred. The amount of the acid catalyst is preferably 0.01 to 10 parts by mass, more preferably 0.2 to 2 parts by mass, relative to 100 parts by mass of the cyclic organosiloxane, α,ω-dihydroxysiloxane oligomer, α,ω-dialkoxysiloxane oligomer, or alkoxysilane.

[0039] The surfactant used in the polymerization includes anionic surfactants such as sodium lauryl sulfate, sodium laureth sulfate, N-acylamino acid salts, N-acyltaurate salts, aliphatic soaps, and alkyl phosphates. Among them, those that are easily soluble in water and do not have a polyethylene oxide chain are preferred. More preferred are N-acylamino acid salts, N-acyltaurate salts, aliphatic soaps, and alkyl phosphates. Particularly preferred are sodium lauroyl methyl taurate, sodium myristoyl methyl taurate, and sodium lauryl sulfate. The amount of the anionic surfactant is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, per 100 parts by mass of the cyclic organosiloxane, α,ω-dihydroxysiloxane oligomer, α,ω-dialkoxysiloxane oligomer, or alkoxysilane.

[0040] The polymerization temperature is preferably 50 to 75° C., and the polymerization time is preferably 10 hours or more, more preferably 15 hours or more. Furthermore, it is particularly preferable to age the polymerization solution after polymerization for 10 hours or more at 5 to 30° C. The pH of the obtained polymerization solution is preferably 6 to 8.

[0041] In the above polymerization reaction, for example, copolymerization of octamethyltetrasiloxane as the cyclic organosiloxane and γ-methacryloxypropylmethyldimethoxysilane as the silane coupling agent is as follows. [ka]

[0042] In the present invention, (ii) acrylic acid ester monomer or methacrylic acid ester monomer (hereinafter sometimes referred to as acrylic component or (meth)acrylic acid ester monomer) is an acrylic acid ester monomer or methacrylic acid ester monomer that does not have a functional group such as a hydroxyl group, an amide group, or a carboxyl group. An acrylic acid ester or methacrylic acid ester having an alkyl group having 1 to 10 carbon atoms is preferred, and a monomer that makes the glass transition temperature (hereinafter sometimes referred to as Tg) of the acrylic component polymer 40°C or higher, preferably 60°C or higher, is more preferred. Examples of such monomers include methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, isopropyl methacrylate, butyl methacrylate, ethyl methacrylate, and cyclohexyl methacrylate. The upper limit of Tg is preferably 200°C or lower, more preferably 150°C or lower. The glass transition temperature can be measured based on JIS K7121.

[0043] The functional group-containing monomer (iii) copolymerizable with the above component (ii) is a monomer having an unsaturated bond including a carboxyl group, an amide group, a hydroxyl group, a vinyl group, an allyl group, etc., and examples thereof include methacrylic acid, acrylic acid, acrylamide, allyl methacrylate, vinyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate. By copolymerizing these, it is possible to improve compatibility.

[0044] The silicone acrylic graft copolymer resin emulsion (II) of the present invention is prepared by emulsion graft polymerization of the polyorganosiloxane (i) obtained as described above with a mixture of a (meth)acrylic acid ester monomer (ii), preferably a monomer (iii) containing a functional group copolymerizable with the component (ii).

[0045] The mass ratio of the polyorganosiloxane of formula (1) to the (meth)acrylic acid ester monomer during graft polymerization (the mass ratio of the polyorganosiloxane of formula (1) to the (meth)acrylic unit) is 50:50 to 90:10, and preferably 70:30 to 90:10. If the silicone component is less than the lower limit of the above mass ratio, sufficient flame retardancy may not be obtained.

[0046] The blending ratio of the above (i) and (ii) components is preferably 1 to 100 parts by mass of the (ii) component relative to 100 parts by mass of the (i) component, more preferably 10 to 100 parts by mass, and even more preferably 40 to 100 parts by mass. In addition, when the above (i) and (ii) components and (iii) components are used, it is preferable to use 1 to 100 parts by mass of the (ii) component and 0.01 to 20 parts by mass of the (iii) component relative to 100 parts by mass of the (i) component, more preferably 10 to 100 parts by mass of the (ii) component and 0.01 to 20 parts by mass of the (iii) component, and even more preferably 40 to 100 parts by mass of the (ii) component and 0.01 to 5 parts by mass of the (iii) component. In this case, it is preferable that the mass ratio of the total of the (ii) component and the (iii) component relative to the mass of the (i) component is 50:50 to 90:10.

[0047] A radical initiator may be used in the above reaction. Examples of the radical initiator include persulfates such as potassium persulfate and ammonium persulfate, hydrogen persulfate water, t-butyl hydroperoxide, and hydrogen peroxide. If necessary, a redox system using a reducing agent such as acidic sodium sulfite, Rongalite, L-ascorbic acid, tartaric acid, sugars, and amines in combination can also be used. The amount of the radical initiator is preferably 0.1 to 5 mass % of the total amount of the components (ii) and (iii), and more preferably 0.5 to 3 mass %.

[0048] Although the surfactant contained in the polyorganosiloxane emulsion described above is sufficient for graft polymerization, anionic surfactants such as sodium lauryl sulfate, sodium laureth sulfate, N-acylamino acid salts, N-acyltaurine salts, aliphatic soaps, and alkyl phosphates can be added to improve stability. Nonionic emulsifiers such as polyoxyethylene lauryl ether and polyoxyethylene tridecyl ether can also be added. When a surfactant is added, the amount used is preferably 0.1 to 5 mass% of the total amount of components (ii) and (iii).

[0049] Furthermore, a chain transfer agent can be added to adjust the molecular weight and graft ratio of the graft polymer.

[0050] The graft polymerization temperature is preferably 25 to 55° C., more preferably 25 to 40° C. The polymerization time is preferably 2 to 8 hours, more preferably 3 to 6 hours.

[0051] The silicone acrylic graft copolymer resin obtained as described above is a polymer in which component (i) is randomly grafted with component (ii) and / or component (iii).

[0052] The silicone acrylic graft copolymer resin of the present invention preferably has a solid content of 30 to 50 mass % in the emulsion. The viscosity of the emulsion (25°C) is preferably 10 to 5,000 mPa·s or less, more preferably 50 to 1,000 mPa·s. The viscosity can be measured by a rotational viscometer. The average particle size of the emulsion is preferably 1 μm or less, more preferably 0.1 μm (100 nm) to 0.3 μm (300 nm). The pH is preferably 6 to 8. The average particle size can be measured by a laser diffraction / scattering type particle size distribution measuring device.

[0053] Since the obtained silicone acrylic graft copolymer resin is in the form of an emulsion, for example, the dispersion is concentrated by a method such as heat dehydration, filtration, centrifugation, or decantation, and then washed with water as necessary. The moisture is removed by heat drying under normal or reduced pressure, spray drying in which the dispersion is sprayed into an air stream, or heat drying using a fluidized heat medium, and the resin is once dried and powdered. The drying temperature is preferably 60 to 105°C. If the obtained powder is slightly aggregated, it may be crushed appropriately using a grinder such as a jet mill, a ball mill, or a hammer mill.

[0054] The silicone acrylic graft copolymer resin may be washed to remove the cyclic organosiloxane and surfactant remaining therein. The solvent used for washing is preferably an alcohol-based organic solvent or a hydrocarbon-based organic solvent, and examples thereof include lower alcohols having 1 to 4 carbon atoms and aliphatic hydrocarbons having 5 to 20 carbon atoms. More specifically, methanol, ethanol, isopropyl alcohol, hexane, and isododecane are more preferable. The washing method is not particularly limited, but for example, 100 parts by mass of the powder is collected in a beaker, and the above-mentioned solvent is added in an amount 5 times or more the mass of the powder, and the mixture is stirred for several hours and then filtered by suction. It is more effective to wash the powder with the same solvent or with a water-soluble solvent such as an alcohol-based solvent. Washing is usually performed at room temperature (25°C), but may be heated depending on the circumstances.

[0055] If the material is washed, it is dried again to form a powder, but the filtered powder may simply be dried in a dryer at a temperature of 40° C. to 200° C. for several hours, or a fluidized bed dryer may be used.

[0056] The silicone acrylic graft copolymer resin thus powdered has an average particle size of 150 μm or less, preferably 10 to 120 μm, and more preferably 10 to 100 μm. The average particle size is measured using a laser diffraction / scattering type particle size distribution measuring device as described above. The weight-average molecular weight of the silicone acrylic graft copolymer resin is preferably 50,000 to 500,000. If it is less than 50,000, precipitation on the surface of the rubber compound may become intense, and even if it exceeds 500,000, the friction reduction effect may be insufficient. The weight average molecular weight is calculated by mixing the emulsion with isopropyl alcohol (IPA), extracting and drying the oil (organopolysiloxane), dissolving 1 g of the mixture in 100 mL of toluene, measuring the kinetic viscosity at 25°C, and converting the value into the molecular weight of dimethyl silicone. More specifically, the calculation is performed using a correlation diagram of the viscosity and weight average molecular weight of dimethyl silicone oil from the viscosity value measured with an Ubbelohde viscometer.

[0057] The glass transition temperature (hereinafter sometimes referred to as Tg) of the silicone acrylic graft copolymer resin is 40° C. or higher, preferably 60° C. or higher, and the upper limit is preferably 200° C. or lower, more preferably 150° C. or lower. The glass transition temperature can be measured according to JIS K7121.

[0058] The amount of the silicone acrylic graft copolymer resin (II) blended is 1 to 20 parts by mass, and preferably 1 to 15 parts by mass, per 100 parts by mass of the polyethylene resin (I). If the amount is less than the lower limit, no improvement in the flame retardancy of the molded article is observed, whereas if the amount is more than the upper limit, the flame retardancy of the molded article may be significantly reduced.

[0059] The flame-retardant resin composition of the present invention may contain various commonly used additives, such as antioxidants, metal deactivators, fillers, lubricants, colorants, ultraviolet absorbers, light stabilizers, and antistatic agents, within the scope of the present invention.

[0060] The antioxidants include amine-based antioxidants such as 4,4'-dioctyl diphenylamine, N,N'-diphenyl-p-phenylenediamine, and 2,2,4-trimethyl-1,2-dihydroquinoline polymers, pentaerythrityl-tetrakis(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate), octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, and 1,3, Examples of such antioxidants include phenol-based antioxidants such as 5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, and sulfur-based antioxidants such as bis(2-methyl-4-(3-n-alkylthiopropionyloxy)-5-t-butylphenyl)sulfide, 2-mercaptobenzimidazole and its zinc salt, and pentaerythritol-tetrakis(3-lauryl-thiopropionate).

[0061] Examples of metal deactivators include N,N'-bis(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyl)hydrazine, 3-(N-salicyloyl)amino-1,2,4-triazole, and 2,2'-oxamidobis-(ethyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate).

[0062] Examples of the filler include carbon, clay, and white carbon.

[0063] Lubricants include hydrocarbons, fatty acids, fatty acid amides, esters, alcohols, and metal soaps, among which Wax E and Wax OP (both trade names, manufactured by Hoechst) are esters, alcohols, and metal soaps that simultaneously exhibit internal and external lubricity. Among these, zinc stearate, magnesium stearate, and calcium stearate are effective in improving insulation resistance, while zinc stearate and magnesium stearate are effective in preventing eye mucus. Furthermore, by using fatty acid amides in combination as a lubricant, it is possible to easily control adhesion to the conductor.

[0064] The flame-retardant resin composition of the present invention can be obtained by melt-kneading the above-mentioned components with a commonly used kneading device such as a twin-screw kneading extruder, a Banbury mixer, a kneader, or a roll. The stirring speed during melt-kneading is preferably 20 to 60 rpm, and the molding temperature is preferably 120°C to 140°C. The molded article obtained from the flame-retardant resin composition of the present invention has an oxygen index of more than 34, preferably more than 35, measured by a method conforming to JIS K 7201-2:2007. The oxygen index is the minimum oxygen concentration required for a material to sustain combustion, and the higher the oxygen index value, the better the flame retardancy. The molded article obtained from the flame-retardant resin composition of the present invention can have excellent combustibility.

[0065] The resin molded article of the present invention can be molded into various shapes such as electric wires and cables, hollow tubes, and sheets. In the case of electric wires, the conductor diameter and the material of the conductor are not particularly limited and are appropriately determined according to the application. The thickness of the coating layer of the resin composition formed around the conductor is not particularly limited either, but is preferably 0.15 to 1 mm. The insulating layer may have a multi-layer structure, and may have an intermediate layer in addition to the coating layer formed with the insulating resin composition of the present invention. In the case of cables, several conductors, optical fibers, etc. coated with the present resin composition on the outside may be bundled and twisted together, and then the resin composition may be coated on the outside, or several conductors, optical fibers, etc. coated with the present resin composition on the outside may be bundled and twisted together, and then the resin composition may be coated on the outside, or several conductors, optical fibers, etc. coated with the present resin composition on the outside may be bundled and twisted together, and then the resin composition may be coated on the outside. EXAMPLES

[0066] The present invention will be described in more detail below with reference to Production Examples, Examples, and Comparative Examples, but the present invention is not limited to the following Examples. In the following Examples, parts and % respectively indicate parts by mass and % by mass.

[0067] The measurement methods used in the following Production Examples and Comparative Production Examples are as follows. <Solid content measurement> Approximately 1 g of each resin emulsion (sample) was accurately weighed onto an aluminum foil dish, placed in a dryer maintained at approximately 105°C, heated for 1 hour, then removed from the dryer and allowed to cool in a desiccator. The sample was then weighed after drying, and the evaporation residue was calculated using the following formula.

number

[0068] <Measurement of average particle size of emulsion> The particle size of the resin emulsion of each example was measured using a laser diffraction / scattering type particle size distribution measuring device (LA950V2) manufactured by Horiba, Ltd.

[0069] <Measurement of glass transition temperature Tg> The glass transition temperature Tg was measured for approximately 1 g of the silicone acrylic copolymer resin powdered by spray drying using a Shimadzu flow tester under a load of 5 kgf at a temperature rise rate of 5° C. per minute.

[0070] <Method for measuring powder particle size> The method for measuring the average particle size in the above examples and comparative examples is as follows. The average particle size was measured using a laser diffraction type particle size measuring instrument (LA-950V2 manufactured by Horiba, Ltd.). In Production Examples 1 to 5, the resin refractive index was set to 1.45, and the methanol refractive index was set to 1.329. The powders obtained in Production Examples 1 to 5 were directly added to the methanol being stirred in the instrument, and the volume-based average particle size of the resin was measured. <Method for measuring weight average molecular weight> The weight average molecular weight of the organopolysiloxane was calculated from the value measured by dissolving 1 g of thoroughly dried organopolysiloxane in 100 mL of toluene with an Ubbelohde viscometer, using a correlation diagram between the kinetic viscosity and the weight average molecular weight of the organopolysiloxane.

[0071] <Production Examples and Comparative Production Examples of Silicone Acrylic Graft Copolymer Resin> [Production Example 1] 600g of octamethyltetracyclosiloxane, 0.48g of γ-methacryloxypropylmethyldiethoxysilane (KBM-502, manufactured by Shin-Etsu Chemical Co., Ltd.), 6g of sodium lauryl sulfate dissolved in 54g of ion-exchanged water, and 6g of dodecylbenzenesulfonic acid dissolved in 54g of pure water were charged into a 2L polyethylene beaker and emulsified uniformly using a homomixer. Then, 490g of water was gradually added to dilute the mixture and the mixture was heated under a pressure of 300kgf / cm. 2 The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. The emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized for 10-20 hours at 55°C. It was then aged for 10-20 hours at 10-20°C, and neutralized to near neutral pH with 12g of 10% aqueous sodium carbonate solution. The silicone emulsion obtained had a non-volatile content of 45.0% after drying for 3 hours at 105°C, and the organopolysiloxane in the emulsion was in the form of a non-fluid soft gel. The organopolysiloxane in the emulsion has a structure represented by formula (1): [ka] R 1 is a methyl group, and R 2is a γ-methacryloxypropyl group, and two of the X's at each end are methyl groups, and the remaining X is a hydroxyl group or a methoxy group. The structures of a, b, and c are shown in Table 1. The weight-average molecular weight is about 250,000. 226 g of methyl methacrylate (MMA) was added dropwise to the silicone emulsion obtained above over a period of 3 to 5 hours, while a redox reaction was carried out with a peroxide and a reducing agent at 30°C, thereby grafting acrylic to the silicone resin component (organopolysiloxane component), and a silicone acrylic graft copolymer resin emulsion with a non-volatile content of 45.2% was obtained. The emulsion was spray-dried (inlet temperature 150°C) using a commercially available spray dryer device to volatilize the volatile content to 1.0%, and a resin powder was obtained.

[0072] [Production Example 2] 600g of octamethyltetracyclosiloxane, 0.48g of γ-methacryloxypropylmethyldiethoxysilane (KBM-502, manufactured by Shin-Etsu Chemical Co., Ltd.), 0.96g of hexamethyldisiloxane, 6g of sodium lauryl sulfate dissolved in 54g of ion-exchanged water, and 6g of dodecylbenzenesulfonic acid dissolved in 54g of pure water were charged into a 2L polyethylene beaker and emulsified uniformly using a homomixer. Then, 490g of water was gradually added to dilute the mixture and the mixture was heated under a pressure of 300kgf / cm. 2 The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. This emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized for 10-20 hours at 55°C. It was then aged for 10-20 hours at 10-20°C, after which the pH was neutralized to near neutral with 12g of a 10% aqueous sodium carbonate solution. After drying for 3 hours at 105°C, the non-volatile content (solid content) of this emulsion was 45.0%, and the organopolysiloxane in the emulsion was in the form of a non-fluid soft gel. The organopolysiloxane in the emulsion has the structure of formula (1) above, R 1 is a methyl group, and R 2 is a γ-methacryloxypropyl group, and X is a methyl group at each end. The structures of a, b, and c are shown in Table 1. The weight-average molecular weight is about 120,000. 226g of methyl methacrylate (MMA) was added dropwise to the silicone emulsion obtained above over a period of 3 to 5 hours while carrying out a redox reaction with a peroxide and a reducing agent at 30°C to graft copolymerize the silicone resin component (organopolysiloxane component) with acrylic, obtaining a silicone acrylic graft copolymer resin emulsion with a non-volatile content of 45.0%. The emulsion was spray-dried (inlet temperature 150°C) to volatilize the volatile content down to 1.0%, obtaining a resin powder.

[0073] [Production Example 3] 600g of octamethyltetracyclosiloxane, 0.48g of γ-methacryloxypropylmethyldiethoxysilane (KBM-502, manufactured by Shin-Etsu Chemical Co., Ltd.), 6g of sodium lauryl sulfate dissolved in 54g of ion-exchanged water, and 6g of dodecylbenzenesulfonic acid dissolved in 54g of pure water were charged into a 2L polyethylene beaker and emulsified uniformly using a homomixer. Then, 490g of water was gradually added to dilute the mixture and the mixture was heated under a pressure of 300kgf / cm. 2 The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. This emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized for 10-20 hours at 55°C. It was then aged for 10-20 hours at 5-10°C, after which the pH was neutralized to near neutral with 12g of a 10% aqueous sodium carbonate solution. After drying for 3 hours at 105°C, the non-volatile content (solid content) of this emulsion was 45.0%, and the organopolysiloxane in the emulsion was in the form of a non-fluid soft gel. The organopolysiloxane in the emulsion has the structure of formula (1) above, R 1 is a methyl group, and R 2 is a γ-methacryloxypropyl group, and at each end, two of the X's are methyl groups, and the remaining X is a hydroxyl group or a methoxy group. The structures of a, b, and c are shown in Table 1. The weight-average molecular weight is about 400,000. 226g of methyl methacrylate (MMA) was added dropwise to the silicone emulsion obtained above over a period of 3 to 5 hours while carrying out a redox reaction with a peroxide and a reducing agent at 30°C to graft copolymerize the silicone resin component (organopolysiloxane component) with acrylic, obtaining a silicone acrylic graft copolymer resin emulsion with a non-volatile content of 45.3%. The emulsion was spray-dried (inlet temperature 150°C) to volatilize the volatile content down to 1.0%, obtaining a resin powder.

[0074] [Production Example 4] 600g of octamethyltetracyclosiloxane, 0.48g of γ-methacryloxypropylmethyldiethoxysilane (KBM-502, manufactured by Shin-Etsu Chemical Co., Ltd.), 6g of sodium lauryl sulfate dissolved in 54g of ion-exchanged water, and 6g of dodecylbenzenesulfonic acid dissolved in 54g of pure water were charged into a 2L polyethylene beaker and emulsified uniformly using a homomixer. Then, 490g of water was gradually added to dilute the mixture and the mixture was heated under a pressure of 300kgf / cm. 2 The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. This emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized for 10-20 hours at 55°C. It was then aged for 10-20 hours at 10-20°C, after which the pH was neutralized to near neutral with 12g of a 10% aqueous sodium carbonate solution. After drying for 3 hours at 105°C, the non-volatile content (solid content) of this emulsion was 45.0%, and the organopolysiloxane in the emulsion was in the form of a non-fluid soft gel. The organopolysiloxane in the emulsion has the structure of formula (1) above, R 1 is a methyl group, and R 2 is a γ-methacryloxypropyl group, and at each end, two of the X's are methyl groups, and the remaining X is a hydroxyl group or a methoxy group. The structures of a, b, and c are shown in Table 1. The weight-average molecular weight is about 250,000. 528g of methyl methacrylate (MMA) was added dropwise to the silicone emulsion obtained above over a period of 3-5 hours while carrying out a redox reaction with a peroxide and a reducing agent at 30°C to graft copolymerize the silicone resin component (organopolysiloxane component) with acrylic, obtaining a silicone acrylic graft copolymer resin emulsion with a non-volatile content of 45.5%. The emulsion was spray-dried (inlet temperature 150°C) to volatilize the volatile content down to 1.0%, obtaining a resin powder.

[0075] [Production Example 5] 600g of octamethyltetracyclosiloxane, 0.48g of γ-methacryloxypropylmethyldiethoxysilane (KBM-502, manufactured by Shin-Etsu Chemical Co., Ltd.), 6g of sodium lauryl sulfate dissolved in 54g of ion-exchanged water, and 6g of dodecylbenzenesulfonic acid dissolved in 54g of pure water were charged into a 2L polyethylene beaker and emulsified uniformly using a homomixer. Then, 490g of water was gradually added to dilute the mixture and the mixture was heated under a pressure of 300kgf / cm. 2 The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. This emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized for 10-20 hours at 55°C. It was then aged for 10-20 hours at 10-20°C, after which the pH was neutralized to near neutral with 12g of a 10% aqueous sodium carbonate solution. After drying for 3 hours at 105°C, the non-volatile content (solid content) of this emulsion was 45.0%, and the organopolysiloxane in the emulsion was in the form of a non-fluid soft gel. The organopolysiloxane in the emulsion has the structure of formula (1) above, R 1 is a methyl group, and R 2 is a γ-methacryloxypropyl group, and at each end, two of the X's are methyl groups, and the remaining X is a hydroxyl group or a methoxy group. The structures of a, b, and c are shown in Table 1. The weight-average molecular weight is about 250,000. 144g of methyl methacrylate (MMA) was added dropwise to the silicone emulsion obtained above over a period of 3 to 5 hours while carrying out a redox reaction with a peroxide and a reducing agent at 30°C to graft copolymerize the silicone resin component (organopolysiloxane component) with acrylic, obtaining a silicone acrylic graft copolymer resin emulsion with a non-volatile content of 44.3%. The emulsion was spray-dried (inlet temperature 150°C) to volatilize the volatile content down to 1.0%, obtaining a resin powder.

[0076] [Production Example 6] 600g of octamethyltetracyclosiloxane, 0.48g of γ-methacryloxypropylmethyldiethoxysilane (KBM-502, manufactured by Shin-Etsu Chemical Co., Ltd.), 6g of sodium lauryl sulfate dissolved in 54g of ion-exchanged water, and 6g of dodecylbenzenesulfonic acid dissolved in 54g of pure water were charged into a 2L polyethylene beaker and emulsified uniformly using a homomixer. Then, 490g of water was gradually added to dilute the mixture and the mixture was heated under a pressure of 300kgf / cm. 2 The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. This emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized for 10-20 hours at 55°C. It was then aged for 10-20 hours at 10-20°C, after which the pH was neutralized to near neutral with 12g of a 10% aqueous sodium carbonate solution. After drying for 3 hours at 105°C, the non-volatile content (solid content) of this emulsion was 45.0%, and the organopolysiloxane in the emulsion was in the form of a non-fluid soft gel. The organopolysiloxane in the emulsion has the structure of formula (1) above, R 1 is a methyl group, and R 2 is a γ-methacryloxypropyl group, and at each end, two of the X's are methyl groups, and the remaining X is a hydroxyl group or a methoxy group. The structures of a, b, and c are shown in Table 1. The weight-average molecular weight is about 250,000. 113g of methyl methacrylate (MMA) and 113g of butyl acrylate (BA) were added dropwise to the silicone emulsion obtained above over a period of 3 to 5 hours while carrying out a redox reaction with peroxide and a reducing agent at 30°C, resulting in acrylic graft copolymerization to the silicone resin component (organopolysiloxane component), and a silicone acrylic graft copolymer resin emulsion with a non-volatile content of 44.9% was obtained. This was spray-dried (inlet temperature 150°C) to volatilize the volatile content down to 1.0%, resulting in a resin powder.

[0077] [Comparative Manufacturing Example 1] 600g of octamethylcyclotetrasiloxane, 0.6g of γ-methacryloxypropylmethyldiethoxysilane (KBM-502, manufactured by Shin-Etsu Chemical Co., Ltd.), 6g of sodium lauryl sulfate dissolved in 54g of pure water, and 6g of dodecylbenzenesulfonic acid dissolved in 54g of pure water were charged into a 2L polyethylene beaker and emulsified uniformly using a homomixer. Then, 470g of water was gradually added to dilute the mixture and the mixture was stirred at a pressure of 300kgf / cm. 2 The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. This emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized at 55°C for 24 hours. It was then aged at 0°C for 24 hours, and then neutralized to near neutrality with 12g of a 10% aqueous sodium carbonate solution to obtain a silicone emulsion. The organopolysiloxane in the emulsion has the structure of formula (1) above, R 1 is a methyl group, and R 2 is a γ-methacryloxypropyl group, and at each end, two of the X's are methyl groups, and the remaining X is a hydroxyl group or a methoxy group. The structures of a, b, and c are shown in Table 1. The weight-average molecular weight is about 250,000. To the silicone emulsion obtained above, 792g of methyl methacrylate (MMA) was added dropwise over 3-5 hours while carrying out a redox reaction with peroxide and reducing agent at 30℃ to graft copolymerize acrylic to the silicone resin component, obtaining a silicone acrylic graft copolymer resin emulsion with a non-volatile content of 45%. By spray drying this, the volatile content was reduced to 1.2%, and a resin powder was obtained.

[0078] [Comparative Manufacturing Example 2] 600g of octamethylcyclotetrasiloxane, 0.6g of γ-methacryloxypropylmethyldiethoxysilane (KBM-502 manufactured by Shin-Etsu Chemical Co., Ltd.), 6g of sodium lauryl sulfate dissolved in 54g of pure water, and 6g of dodecylbenzenesulfonic acid dissolved in 54g of pure water were charged into a 2L polyethylene beaker and emulsified uniformly using a homomixer. Then, 470g of water was gradually added to dilute the mixture and the mixture was stirred at a pressure of 300kgf / cm. 2 The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. This emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized at 55°C for 24 hours. It was then aged at 0°C for 24 hours, and then neutralized to near neutrality with 12g of a 10% aqueous sodium carbonate solution to obtain a silicone emulsion. The organopolysiloxane in the emulsion has the structure of formula (1) above, R 1 is a methyl group, and R 2 is a γ-methacryloxypropyl group, and at each end, two of the X's are methyl groups, and the remaining X is a hydroxyl group or a methoxy group. The structures of a, b, and c are shown in Table 1. The weight-average molecular weight is about 250,000. 28g of methyl methacrylate (MMA) was added dropwise to the silicone emulsion obtained above over a period of 3-5 hours while a redox reaction was carried out with peroxide and a reducing agent at 30℃, resulting in acrylic graft copolymerization to the silicone resin component, and a silicone acrylic graft copolymer resin emulsion with a non-volatile content of 44.2% was obtained. This was spray-dried to volatilize the volatile content down to 1.2%, resulting in a resin powder.

[0079] Table 1 shows the constitution and physical properties of the organopolysiloxane in the emulsion, the physical properties of the emulsion, and the physical properties of the obtained silicone acrylic graft copolymer resin in the above Production Examples and Comparative Production Examples. [Table 1]

[0080] <Forming method> Examples 1 to 7, Comparative Examples 1 to 2 Ethylene-ethyl acrylate copolymer (EEA resin, product name: NUC-6520, Eneos NUC), magnesium hydroxide (product name: Magseeds S, Konoshima Chemical Co., Ltd.), and the resin powder obtained in the examples or comparative examples were kneaded in the amounts shown in the table below at approximately 120°C and 50 rpm in a kneader, pressed into plates of approximately 4 mm thickness, and cut to obtain test pieces. The oxygen index, appearance, static and dynamic friction coefficient, and tactile feel of the resulting molded products were evaluated. The results are shown in Tables 2 and 3. The density of the EEA resin used in the examples and comparative examples was 0.94 g / cm 3 The melt mass flow rate at 190°C under a load of 2.16 kg, measured in accordance with JIS K7210-1:2014, is 1.6 g / 10 min, the ethyl acrylate content is 24 mass%, and the durometer hardness (D) is 85. The magnesium hydroxide used in the examples and comparative examples was magnesium hydroxide for flame retardant use, which had been surface-treated with a silane coupling agent, and had an average particle size of 1.0 μm.

[0081] The measurement methods used in the examples and comparative examples are as follows. <Oxygen Index Test> For the above test pieces, the oxygen index of the molded body was measured by a method in accordance with JIS K 7201-2:2007. Sample shape: I-shape 80 x 10 x 4 mm Test conditions: Method A Measurement equipment: Candle combustion tester AC2 type used Flammability was evaluated based on the oxygen index obtained. The higher the oxygen index, the better the flame retardancy.

[0082] <Appearance> The appearance of the molded pieces was visually observed. ◯: A clean molded piece without any agglomerates. ×: Aggregates were observed

[0083] <Static and dynamic friction coefficient measurement> Using a HEIDON TYPE-38 (manufactured by Shinto Scientific Co., Ltd.), a 200 g metal indenter was brought into contact perpendicularly with the coating film of each of the above examples and moved at 3 cm / min. The frictional force was measured, and the static and kinetic friction coefficients were calculated from the frictional force.

[0084] <Tactile sensation> When the static friction coefficient obtained by the static and dynamic friction coefficient measurement was less than 0.55, the dynamic friction coefficient was less than 0.50, and the difference between the static and dynamic friction coefficients was 0.05 or less, the tactile evaluation of the molded product was rated as "good." A molded product rated as "good" for tactile evaluation has better surface slipperiness than a molded product rated as "poor."

[0085] [Table 2]

[0086] [Table 3] [Industrial Applicability]

[0087] As described above, the molded article made of the flame-retardant resin composition of the present invention has excellent flame retardancy and touch. The molded article made of the flame-retardant resin composition of the present invention can be molded into various shapes such as hollow tubes and sheets, and is suitable for use as a covering film for electric wires and cables.

Claims

1. A flame-retardant resin composition comprising the following components (I), (II), and (III): (I) Polyethylene resin: 100 parts by mass, (II) inorganic flame retardant: 50 to 300 parts by mass, and (III) 1 to 20 parts by mass of a silicone acrylic graft copolymer resin which is a copolymer of a polyorganosiloxane represented by the following formula (1) and at least one monomer selected from an acrylic acid ester monomer and a methacrylic acid ester monomer, and in which the mass ratio of the polyorganosiloxane to the acrylic acid ester unit and the methacrylic acid ester unit is 50:50 to 90:10: A flame-retardant resin composition comprising 【Chemistry 1】 (In the formula, R 1 are each independently a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms; R 2 is a mercapto group, an alkyl group having 1 to 6 carbon atoms having an acryloxy group or a methacryloxy group, or a vinyl group; X's are each independently a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a hydroxyl group; a is a positive number from 1 to 10,000; b is a positive number from 0.1 to 1,000; and c is 2; provided that the bonding order of the siloxane units in the above formula (1) is not limited to the above.

2. In the above formula (1), R 1 and at least one of X at both ends is, independently of each other, a linear, branched or cyclic alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms.

3. 3. The flame-retardant resin composition according to claim 1, wherein at least two of X in the formula (1) are hydroxyl groups or alkoxy groups.

4. 2. The flame-retardant resin composition according to claim 1, wherein the silicone acrylic graft copolymer resin has an average particle size of 150 μm or less.

5. The silicone acrylic graft copolymer resin is (i) a polyorganosiloxane represented by the above formula (1); (ii) an acrylic acid ester monomer or a methacrylic acid ester monomer; (iii) a functional group-containing monomer copolymerizable with the optional (ii) component; 2. The flame-retardant resin composition according to claim 1, which is a copolymer of the above.

6. The flame-retardant resin composition according to claim 1, wherein the polyethylene-based resin is at least one selected from the group consisting of ethylene polymers, random copolymers of ethylene and one or more α-olefins other than ethylene, block copolymers of ethylene and one or more α-olefins other than ethylene, ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid ester copolymers, and ethylene-(meth)acrylic acid copolymers.

7. 2. The flame-retardant resin composition according to claim 1, wherein the inorganic flame retardant is selected from the group consisting of metal hydroxides, surface-treated metal hydroxides, metal oxides, metal carbonate compounds, metal powders, boron compounds, and low-melting glass.

8. 8. The flame-retardant resin composition according to claim 7, wherein the inorganic flame retardant is a metal hydroxide which has been surface-treated with a higher fatty acid or a silane coupling agent.

9. A tubular or sheet-shaped molded article comprising the flame-retardant resin composition according to any one of claims 1 to 8.

10. An electric wire having a layer made of the flame-retardant resin composition according to any one of claims 1 to 8.

11. A cable having a layer made of the flame-retardant resin composition according to any one of claims 1 to 8.